Pengaruh Hilirisasi Sumber Daya Alam Terhadap Kesejahteraan Pelaku Usaha Dalam Persepektif Ekonomi Islam Pada Industri Singkong Di Kabupaten Lampung Timur - Hasanah, Nur; mansyah, Budi; Zulaikah (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
Downstreaming is the process of processing natural resources into value-added products to improve community welfare. This study aims to analyze the impact of natural resource downstreaming on the welfare of business actors from an Islamic economic perspective in the cassava industry in East Lampung Regency. This study used a quantitative method with primary data, and data collection was conducted through questionnaires and limited interviews with cassava industry business actors. The results show that natural resource downstreaming has a positive impact on the welfare of business actors. This is evidenced by increased income, expanded employment opportunities, and strengthened local economies. This research is expected to broaden insights and improve natural resource downstreaming in the region.